Problematika dalam Penerapan Kurikulum Merdeka pada SDN 108611 Bandar Setia - Engelina Nababan; Salwa Huda Muliana Hasibuan; Sonya Mika; Tasya Amanda Putri (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
This study aims to analyze the problems experienced by elementary school teachers at SDN 108611 Bandar Setia in implementing the independent curriculum. This research method uses a qualitative method, where this study collects data from the results of interviews with one of the grade 6 teachers at SDN 108611 Bandar Setia. This study also collects data through literature studies. The subjects in this study were grade 6 teachers. The results of this study show that whatever the problems are, there must be solutions in them, therefore through this study it can be concluded with solutions that can be done by a teacher in implementing this independent curriculum during teaching and learning activities.